DEVELOPING A MEASURE OF COMMUNITY-LEVEL DEMENTIA FRIENDLINESS IN FAITH COMMUNITIES. (20th December 2022) - Epps, Fayron; Bender, Alexis; Gore, Janelle; Gunn, Grayson; Markert, Dana; Moore, Miranda
Abstract: As the prevalence of dementia rises, modifying built and social environments of persons living with dementia (PLWD) becomes increasingly essential. Although there is a call to rigorously evaluate dementia-friendly community initiatives, no known comprehensive evaluation tools exist to assess small communities (churches and community centers). Therefore, we are developing a person-centered Dementia-Friendly Community Assessment tool. This tool will consist of new and validated scales to assess the level of dementia-friendliness among churches enrolled in a dementia-friendly congregation program based in African American communities. A draft of a theory-informed survey instrument is being shared with stakeholders (church leaders, caregivers, and PLWD) during focus groups who will provide feedback on their understanding and relevance of questions on the instrument. The tool will then be modified based on feedback and the final instrument will be piloted with broad church membership. Our aim is to enable programs to quantify their dementia-friendly community initiative's impact.